How Accurate is Intraoperative Alignment Measurement with a Navigation System in Primary Total Knee Arthroplasty? - Feichtinger, Xaver; Kolbitsch, Paul; Kocijan, Roland; Baierl, Andreas; Giurea, Alexander (The Journal of Knee Surgery, 2018)
The primary objective was to compare the intraoperative data assessed by OrthoPilot (Aesculap AG, Tuttlingen, Germany) with postoperative coronal and sagittal long-leg standing radiographs. The secondary objective was to evaluate the influence of sex and body mass index (BMI) on the accuracy and effectiveness of the implantation of the knee prosthesis by OrthoPilot. We included 75 patients in our investigation. Participants received an e.motion (Aesculap AG) knee prosthesis using the OrthoPilot navigation system. Postoperative long-leg standing anteroposterior and lateral radiographs were performed. We compared the intraoperative navigational data with postoperative determined angles of knee geometry. We also compared the sex and BMI of participants to their difference between intraoperative and postoperative measurements to test for an association. We found a difference between intraoperative data and radiographs of 1.8 degrees for the hip-knee-ankle angle. The intraoperative lateral distal femoral angle and medial proximal tibial angle differed from the radiological analysis by 1.2 degrees, respectively. The lateral views revealed a difference of 1.6 degrees for femur lateral and 1.4 degrees for the tibia lateral. There was no significant (p > 0.05) influence of the parameters BMI and sex of the patients on these values. Our results showed that the implemented intraoperative navigation system is reliable. It does not differ on average from postoperative radiographs by more than 1.8 degrees. The findings of our study suggest that a correct postoperative alignment can be achieved in both high and low BMI participants if a precise range is maintained during the surgery.
Keywords: total knee arthroplasty; navigation; long-leg standing radiographs; alignment; BMI